A DFT investigation of optoelectronic properties of CdMgS2 compound. (2023) - Sharma, Shikha; Khan, Karina; Ahuja, Ushma; Soni, Amit; Sahariya, Jagrati
Abstract: The motive of our study is to look at the optoelectronic characteristics of CdMgS2 compound for exploring its utility for photovoltaic devices. The optical optoelectronic properties and structural properties of CdMgS2 compound are evaluated by DFT incorporate on the Wien2k software. The PBE-GGA has been taken into account when conducting the first principle method. With the help of its band structure and density of state, the electronic characteristics of CdMgS2 are determined. According to our research, band gap of CdMgS2 is 2.1 eV. CdMgS2 optical properties are discussed through its optical parameters. The computed absorption coefficient value is 79.947 (×10 4 eV/cm) which shows that the CdMgS2 is suitable for optoelectronic applications.